1991
DOI: 10.1128/aem.57.11.3187-3192.1991
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of animal infectivity, excystation, and fluorogenic dye as measures of Giardia muris cyst inactivation by ozone

Abstract: Giardia muris cyst viability after ozonation was compared by using fluorescein diacetate-ethidium bromide staining, the C3H/HeN mouse-G. muris model, and in vitro excystation. Bench-scale batch experiments were conducted under laboratory conditions (pH 6.7, 22°C) in ozone-demand-free phosphate buffer. There was a significant difference between fluorogenic staining and infectivity (P c 0.05), with fluorogenic staining overestimating viability compared with infectivity estimates of viability. This suggests that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
7

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 17 publications
1
18
0
7
Order By: Relevance
“…The single cyst that was resistant to dye penetration caused considerable alarm because it was found in a treated water sample. This situation is the same as that discussed by Labatiuk et al (20) who concluded that viable cysts as indicated by fluorogenic dyes may not be able to complete their life cycle and produce an infection. The actual risk of giardiasis infection presented by this possibly viable cyst must have been low, because there was no detectable increase in human cases of giardiasis in the months following the report of the positive sample.…”
Section: Viability and Infectivitysupporting
confidence: 77%
See 1 more Smart Citation
“…The single cyst that was resistant to dye penetration caused considerable alarm because it was found in a treated water sample. This situation is the same as that discussed by Labatiuk et al (20) who concluded that viable cysts as indicated by fluorogenic dyes may not be able to complete their life cycle and produce an infection. The actual risk of giardiasis infection presented by this possibly viable cyst must have been low, because there was no detectable increase in human cases of giardiasis in the months following the report of the positive sample.…”
Section: Viability and Infectivitysupporting
confidence: 77%
“…Water treatment studies have shown that viability testing by nucleic acid staining is not well correlated with animal infection experiments at high levels of water treatment and low numbers of cysts. (20,21) Dye exclusion can, however, be a good indicator of viability in the absence of disinfectants. (22,23) Because penetration of cells by nucleic acid dyes demonstrates abnormal membrane permeability rather than the status of metabolic activity, a cell that admits dye may not yet be dead and could cause an infection if ingested.…”
Section: Viability and Infectivitymentioning
confidence: 99%
“…Using human isolates, FDA staining consistently overestimated cyst viability, and this probe was found to be totally unreliable in predicting the viability of C. parvum when compared with animal infection tests (17). Labatiuk et al (18), using cyst samples inactivated by ozone, also found a significant difference between the FDA-staining method and the animal infectivity test for G. muris.…”
Section: Introductionmentioning
confidence: 99%
“…Evaluating the public health risk by the application of viability dyes is considered inaccurate as it seems to lack reproducibility when conducted in different laboratories (Clancy et al 1994) and, like IFA, does not enable speciation. In vitro excystation (Rice and Schaefer 1981) and subjecting cysts to animal infectivity models (Labatiuk et al 1991) are considered too expensive, time consuming and impractical to be employed for routine testing of water supplies. Such animal or in vitro methods also may not correlate with infectivity in humans.…”
Section: Introductionmentioning
confidence: 99%